YOUTUBE AS ALTERNATIVE MEDIA CAREER GUIDANCE - Kharis Efendi (Universitas Sultan Ageng Tirtayasa, 2022)
Technology is changing the face of education. Not all BK teachers use the media to implement career guidance, and YouTube is a suitable medium. This study resulted in the concept of YouTube media to support the implementation of career guidance services. The qualitative literature study approach uses descriptive analysis through the stages of data reduction, presenting data, and interpreting data using primary documents from journals, books, and relevant scientific articles published in 2020-2022. The concept of using YouTube in career guidance is informational video content and video tutorials, vlogs, podcasts, and films. YouTube media can be a creative guidance method to express and develop student abilities. YouTube media can apply guidance and counselling teachers to support guidance and counselling services, especially career guidance services.